Genes and Podocytes – New Insights into Mechanisms of Podocytopathy - Bierzynska, Agnieszka; Soderquest, Katrina; Koziell, Ania (Frontiers in Endocrinology, 2015)
After decades of primarily morphological study, positional cloning of the NPHS1 gene was the landmark event that established aberrant podocyte genetics as a pivotal cause of malfunction of the glomerular filter. This ended any uncertainty whether genetic mutation plays a significant role in hereditary nephrotic syndromes and confirmed podocytes as critical players in regulating glomerular protein filtration. Although subsequent sequencing of candidate genes chosen on the basis of podocyte biology had less success, unbiased analysis of genetically informative kindreds and syndromic disease has led to further gene discovery. However, the 45 genes currently associated with human nephrotic syndrome explain no more than 20-30% of hereditary and only 10-20% of sporadic cases. It is becoming increasingly clear both from genetic analysis and phenotypic data - including occasional response to immunosuppressive agents and post-transplant disease recurrence in Mendelian disease - that monogenic inheritance of abnormalities in podocyte-specific genes disrupting filter function are only part of the story. Recent advances in genetic screening technology combined with increasingly robust bioinformatics are set to allow identification and characterisation of novel disease causing variants and more importantly, disease modifying genes. Emerging data also supports a significant but incompletely characterised immunoregulatory component.